PERENCANAAN KEUANGAN SYARIAH BAGI KELUARGA PADA DESA CIMAYANG KECAMATAN PAMIJAHAN, KABUPATEN BOGOR - Trihantana, Rully; Rizal, Muhammad; Lusita (SAHID DEVELOPMENT JOURNAL : Jurnal Pengabdian Kepada Masyarakat Perbankan Syariah, 2023)
Implementation of the sharia economy should be directed not only focused on banking activities. Sharia economic system is intended to provide benefits to the economy as a whole, including the management of family finances. Any religion in line with this concept is primarily Islamic as a mercy to the universe. This community service program aims to socialize sharia economy in family financial management, by from Village of Cimayang Pamijahan Bogor learning in assemblies. The result shows the spirit to immediately implement the sharia family financial planning.